USING COMMUNICATION TECHNOLOGY IN EDUCATION: OPPORTUNITIES AND CHALLENGES - Loso Judijanto; Muhdi Late; Novianty Djafri (Jurnal Komunikasi, 2024)
In the current digital era, the integration of communication technology in education has become the main key to reforming teaching and learning methods. The use of technology such as the Internet, e-learning platforms, and various digital communication tools has opened up new opportunities for more inclusive and effective learning approaches. This research aims to explore the opportunities offered by communication technology in education as well as the challenges faced in its implementation. The research method used was a literature review. The research results show that the use of communication technology significantly increases the accessibility of learning materials, enriches the learning experience through interactive resources, and allows personalization of the learning process according to individual needs. However, the study also identified several significant challenges, such as the digital divide, the additional burden for teachers in mastering new technologies, data security, and challenges in keeping students engaged in online learning